ПРОБЛЕМИ ТА АСПЕКТИ ПРОЕКТУВАННЯ КЛАСТЕРИЗАЦІЇ МІКРОМЕРЕЖ - Федосеєнко, О.М. (Інститут електродинаміки Національної академії наук України, 2023)
With the growing penetration of distributed energy resources, the traditional microgrid concept is evolving into microgrid clustering, which decomposes the distribution system into interconnected microgrids to improve stability, reliability, and efficiency. Microgrid clusters coordinate power sharing between microgrids and the main grid, effectively reducing problems such as voltage rise, harmonics, poor power factor, reverse power flow, and conventional protection scheme failures. However, there are challenges to overcome before adopting microgrid clustering, particularly in the design aspects. This paper critically reviews the challenges in the design of microgrid clustering, categorizing multi-microgrids into different architectures based on the interconnections' layout, evaluating reported control techniques in microgrid clustering, and presenting aspects of multi-microgrid protection. Possible areas of future research are highlighted to improve the operational aspects of microgrid clusters.